Blood disease diagnosis / Noor Hayati Nan - Nan, Noor Hayati (2003)
The purpose of this study is to apply the idea of Integrated Diagnosis System to the blood disease diagnosis where work is concentrated on the integrated of the rule based in certainty factor theory. This thesis can help the user by providing an expert system that takes into consideration to find the disease and presents identification as a possible treatment. The information about the symptom or blood test or both of this information will require. The reasoning of the result will come out together. The topics covered in this thesis including the introduction of system in general and details discussion of the applications, the method that been used in order to complete the project, the result, conclusion and some recommendation needs to be applied for a future.